Kaléidoscope : l'instrumentalisation du problème de la drogue dans les Amériques - Fortmann, Michel; Aureano, Guillermo; Lopez, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
The purpose of this article is to shed new light on the issue of drug trafficking in the Americas. Specifically its objective is to demonstrate that the perception of drug trafficking as a national security threat is only one aspect of a much more complex socio-political phenomenon. First, this paper presents the multilateral mechanisms that serve as a frame work to facilitate regional cooperation on drug matters. It goes on to analyze the different approaches of regional drug trafficking. It concludes that a much more flexible approach is needed to gain an in-depth understanding of drug politics in the Americas.